Molecular Cloning of Ccoaomt Genomic Sequence From Acacia Mangium Superbulk Trees Via PCR - Kho, Tieng Tieng (Universiti Malaysia Sarawak (UNIMAS), 2010)
Acacia mangium is an adaptable and fast growing tropical tree which was first introduced to Malaysia in 1960s for the purpose of producing general utility timber (Sahri et al., 2002). The species has become a major plantation tree species in Southeast Asia since the last two decades. The species is economic importance as the wood can be used for production of furniture, veneers, plywood, pulp and paper making. Besides, A. mangium is being widely used for reforestation and soil rehabilitation in degraded soil due to its ability to associate with soil rhizobia and fix nitrogen from atmosphere. Acacia mangium superbulk is a genetic improved clone of Acacia mangium with more excellent traits (Tchin, 2009).